Sources of post-pandemic inflation in Germany and the euro area: An application of Bernanke and Blanchard (2023) - Jan-Oliver Menz (Deutsche Bundesbank, 2024)
We use a simple macroeconomic model proposed by Bernanke and Blanchard (2023) to investigate the reasons for the recent sharp rise in inflation. Applied to Germany and the euro area, the model suggests that the surge in inflation has mainly been caused by commodity price shocks and supply bottlenecks, rather than shortages in the labour market. Inflation expectations were found to be well-anchored and evidence for a wage-price spiral is scarce. The model predicts a gradual decline in future inflation rates. However, this prediction is based on the assumption that there will be no commodity price shocks and that the labour market will cool down.
Keywords: E3; J3; D84; C33; 330; Inflation; wages; inflation expectations; Phillips curve